From the concept to the concrete lawyer and the person - Kamenkov, Victor S. (Journal of the Belarusian State University. Law, 2019)
The proposed article analyzes the objective principles and assumptions, as well as the formal reasons that have become the basis for the development and adoption of the Concept of the development of legal education in the Republic of Belarus for the period up to 2025. Its characteristic features, scientific novelty, practical importance, as well as its conformity to the Constitution of the Republic of Belarus, continuity with the current Education Code and international standards in the field of legal education are singled out.